2022
DOI: 10.3389/fendo.2022.856268
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Models for Elderly (≥70 Years Old) Primary Operable Triple-Negative Breast Cancer: Analysis From the National Cancer Database

Abstract: BackgroundTriple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer. In the elderly (≥70 years old) primary operable (T1-3N0-1M0) TNBC, individualized treatment modalities for this population are pivotal and important, but limited studies are explored.MethodsThe clinicopathological features of elderly primary operable TNBC patients were retrospectively selected from the Surveillance, Epidemiology, and End Results (SEER) database between January 2010 and December 2015. Kaplan–Meier curves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This benefit persisted after stratification for node-negative BC (HR=0.80, p=0.007), node-positive BC (HR=0.76, p=0.006), and those with a comorbidity score >0 (HR=0.74, p=0.013). In the same way, Tang et al (79) have shown in elderly primary operable TNBC patients (≥70 years old) that age (HR=1.03 per year, p<0.001), T1c (HR=2.95) and chemotherapy (HR=0.79, p=0.035) were associated with lesser cancer-specific survival.…”
Section: Elderly Patient Outcomesmentioning
confidence: 66%
“…This benefit persisted after stratification for node-negative BC (HR=0.80, p=0.007), node-positive BC (HR=0.76, p=0.006), and those with a comorbidity score >0 (HR=0.74, p=0.013). In the same way, Tang et al (79) have shown in elderly primary operable TNBC patients (≥70 years old) that age (HR=1.03 per year, p<0.001), T1c (HR=2.95) and chemotherapy (HR=0.79, p=0.035) were associated with lesser cancer-specific survival.…”
Section: Elderly Patient Outcomesmentioning
confidence: 66%
“…There are already many predictive models for the all-cause death of breast cancer based on the SEER database. We found that their overall prediction C statistic was between 0.70 and 0.72 ( 20 , 21 ). In addition, we found that, when their all-cause mortality models were constructed, the SEER predictors did not include some of the basic diseases of the patients and some regular indicators at the time of hospitalization.…”
Section: Discussionmentioning
confidence: 94%
“…There are other gene score-based predictive models, including Oncotype DX and MammaPrint; however, these models have not been adequately validated in the elderly breast cancer population, as most of the patients recruited in these studies were under 65 years old (29, 30). Recently, there have been some novel prognostic models for elderly patients with breast cancer (31,32); however, the data for these nomograms from public databases were heterogeneous and the model was applicable to specialized groups such as patients with TNBC (31) or metastasis (32). The predictive model constructed in our study included not only the main clinicopathological features such as T stage, N stage, KI-67 status, and primary treatment methods such as operation type, but also chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%